Albanian university students' knowledge, attitudes, and practices regarding COVID-19 infection and vaccine: A cross-sectional study - Lumturi Merkuri; Edmond Puca; Fatjona Kamberi; Ilir Alimehmeti; Erda Qorri; Xhejni Borshi (Journal of Infection in Developing Countries)
Introduction: COVID-19 pandemic remains a public health concern worldwide. Given that, students represent a subgroup of the population with an impact on the pandemic.